2017
DOI: 10.5812/amh.66590
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Stimulated Saliva C-reactive Protein Changes in Altitude Chamber

Abstract: Objectives: The object of the research was to examine stimulated saliva and serum C-reactive protein (hs-CRP) prior and following the experience of hypobaric hypoxia process (EHHP) in an altitude chamber in aviators.Methods: A total of 40 healthy aircrew (age: 31.8 ± 6.0 years; BMI: 25.6 ± 2.7 Kg/cm 2 ) experienced hypobaric chamber. Hs-CRP levels were assayed in stimulated whole saliva and serum before and after intervention by the ELISA method and were statistically analyzed by the paired student's t test.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…According to some authors, hs-CRP could be a valid and independent predictor of cardiac attack, cardiac arrest due to vascular obstruction, and vascular diseases. Mirzaii-Dizgah et al revealed that the mean serum hs-CRP concentration significantly increased following the hypobaric hypoxia process (EHHP) in an altitude chamber (before: 1.78 ± 0.33 µg/mL vs. after: 2.58 ± 0.45 µg/mL) ( p = 0.02) [ 65 ]. Due to this fact, hs-CRP should be considered as a useful biomarker in military pilots, as they experience hypoxia during flight.…”
Section: Inflammationmentioning
confidence: 99%
“…According to some authors, hs-CRP could be a valid and independent predictor of cardiac attack, cardiac arrest due to vascular obstruction, and vascular diseases. Mirzaii-Dizgah et al revealed that the mean serum hs-CRP concentration significantly increased following the hypobaric hypoxia process (EHHP) in an altitude chamber (before: 1.78 ± 0.33 µg/mL vs. after: 2.58 ± 0.45 µg/mL) ( p = 0.02) [ 65 ]. Due to this fact, hs-CRP should be considered as a useful biomarker in military pilots, as they experience hypoxia during flight.…”
Section: Inflammationmentioning
confidence: 99%